Sam Shepard and the “Familial Maze”: possible worlds theory in Buried Child - Amani, Omid; Pirnajmuddin, Hossein; Marandi, Seyed Mohammad (Penerbit Universiti Kebangsaan Malaysia, 2017)
The present paper attempts to address Sam Shepard’s treatment of American family in Buried Child focusing on 'world construction.' In order to explore the process of world creation in the play, the writers draw on the works of Marie-Laure Ryan, a key theorist in 'possible worlds theory,' one of the orientations in cognitive poetics. Considering Shepard's highlighting of the bonds among the family members figuring in his plays, the interactions of characters with Textual Actual World (henceforth TAW) are of paramount importance and contribute to what Ryan calls 'tellability.' Central to our analysis is the consideration of the characters’ private worlds’ interactions and their intrafamilial and extrafamilial conflicts. Shepard is also centrally concerned with American (popular) culture and its underlying myths, hence the prominence of the theme of American Dream in his oeuvre. As such, the projection of the characters’ wish worlds is central in Shepard's play. Considering these “wish worlds” in terms of possible worlds-theory could be rewarding. Many of these wish worlds, it is argued, hinge on the notion of American family whose consideration by Shepard stems from his interest in the questions of origins, identity, selfhood, and autonomy.